The protection of a wife’s rights against the elements of narcissism and gaslighting in domestic violence: The impact during COVID-19 pandemic - Ismail, Sukriah; Urus, Nur Sarah Tajul; Binawae, Farida Isa; Siraji, Ahmad Hussein Abdul Shakoor (Linguistics and Culture Review, 2021)
This study constructively focused on the polemic in a household regarding the impact of the COVID-19 pandemic that hits the world. For example, China experienced a high number of divorce cases during the emergency order period. In Malaysia, during the Movement Control Order (PKP), a number of wives lodged a significant number of complaints of conflict or domestic violence to the Malaysian Islamic Development Department (JAKIM). This indicates the existence of domestic conflict on a large scale. This study is timely to examine the causes of domestic violence conflict. The second objective is to identify the rights of wives in the household and the third, to propose a standard procedure of a nurturing household to the State Religious Affairs Department. This study used a qualitative methodology. The content analysis method was used with materials that were significantly library-sourced consisting of primary and secondary data. Primary data were collected from the book of fiqh to clarify the rights and responsibilities of the wife in the household. Secondary data is based on published material, such as textbooks, journal articles, online databases and the Internet. For analysis, this study used a combination of data analysis methods, namely descriptive, critical and comparative approaches.